Pengembangan Mutu Lulusan Melalui Program Guru Tugas di Pondok Pesantren: Studi Kasus di Lembaga Pendidikan Islam Darul Ulum Banyuanyar Pondok Pesantren Banyuanyar dan Pondok Pesantren Mambaul Ulum Bata-Bata Pamekasan - Ghazali, Ziyadul Ifdhal (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
So far, Islamic boarding schools have been perceived as marginalized caste educational institutions and are below the level of general education. This is due to the quality of the graduates who are considered by most people will not be able to compete in facing the challenges of the times. Moreover, Islamic boarding schools are only considered capable of producing graduates of prospective ustad or preachers so that it strengthens the community's assumption that pesantren graduates are not competitive in the job market. This assumption cannot be fully justified or blamed due to the fact that Islamic boarding schools as educational institutions are complex phenomena. In Islamic boarding schools, students not only get religious education, but also other sciences as a provision for students to face their life in society. There is an interesting fact, that in some Islamic boarding schools there is a graduate quality development program called the task teacher program to maintain the quality standards of boarding school graduates. The task teacher program is packaged by the pesantren as a forum for community service for students in the third grade of Madrasah Aliyah (MA) and the equivalent after carrying out the National Examination (UN) to carry out da'wah missions as well as become ambassadors for the pesantren. The students will then be placed in various regions for one year. In the place of duty, the students are required to implement the knowledge they have gained while at the Islamic boarding school. The task teacher program is packaged by the pesantren as a forum for community service for students in the third grade of Madrasah Aliyah (MA) and the equivalent after carrying out the National Examination (UN) to carry out da'wah missions as well as become ambassadors for the pesantren. The students will then be placed in various regions for one year. In the place of duty, the students are required to implement the knowledge they have gained while at the Islamic boarding school. The task teacher program is packaged by the pesantren as a forum for community service for students in the third grade of Madrasah Aliyah (MA) and the equivalent after carrying out the National Examination (UN) to carry out da'wah missions as well as become ambassadors for the pesantren. The students will then be placed in various regions for one year. In the place of duty, the students are required to implement the knowledge they have gained while at the Islamic boarding school.